Thermal effects and dynamical hysteresis in the turn-on and turn-off of vertical-cavity surface-emitting lasers - Hong, Yanhua (2010)
Thermal effects and dynamical hysteresis in VCSELs under dc modulation have been experimentally studied. The results show that the VCSEL turn-on and turn-off currents can display both positive hysteresis and negative hysteresis, depending on the current modulation frequency and on the substrate temperature. Numerical simulations of semiconductor laser rate equations, extended to take into account thermal effects, show a good agreement with the observations.